Life style and interpersonal values according to young people personality from Huanuco departament - Campos C., Lilia (2009)
The work has the the objective of determining how way the life style and interpersonal values differ each other accordint to tha category that each youg people from Huanuco Department obtains into from each personality factor of Caprara and Barbaranelli. The used method was the Correlational Descriptive, the sample was conformed for 374 both sex young people and responded the next tests: BFQ Questionary, the Interpersonal Values Questionary and the Life Style Questionary. The Validity and Trusting of these tests were shown and adapted to eruvian scales. The results show that personality factors from Big Five don’t set out significative difference over life styles and interpersonal values.